High treatment resistance is associated with lower performance in the Stroop test in patients with obsessive–compulsive disorder - Doolub, Damien; Vibert, Nicolas; Botta, Fabiano; Razmkon, Ali; Bouquet, Cédric; Wassouf, Issa; Millet, Bruno; Harika-Germaneau, Ghina; Jaafari, Nematollah (Frontiers in Psychiatry, 2023)
Around 50 percent of the patients with obsessive-compulsive disorder (OCD) are resistant to treatment, and patients with OCD show alterations in a broad range of cognitive abilities. The present study investigated the links between treatment-resistance, executive and working memory abilities, and the severity of OCD symptoms among 66 patients with OCD. The patients performed seven tests gauging their executive functions and working memory and filled in questionnaires for OCD severity and insight into their pathology. In addition, the executive and working memory abilities of a subset of these patients were compared with those of individually matched control participants. In contrast with previous studies, patients’ treatment resistance was evaluated by considering the clinical outcomes of all the treatments that they received during the course of their disease. Higher treatment resistance was associated with lower performance in one particular executive test, the Stroop test, which assessed patients’ ability to inhibit prepotent/automatic responses. Older age and more severe OCD symptoms were also associated with higher treatment resistance. Regardless of OCD severity, the patients displayed small to moderate deficits across most components of executive functions compared to control participants. Interestingly, patients with OCD took more time than control participants to perform speeded neuropsychological tests but never made more errors. Altogether, this study shows that the treatment-resistance of patients with OCD may be reliably quantified over the course of years and treatments using Pallanti and Quercioli’s (2006) treatment resistance-related scales. The data suggest that the Stroop test could be used clinically to anticipate treatment outcomes in to-be-treated patients.